Wage determination in the long run, real wage resistance and unemployment: Multivariate analysis of cointegrating relations in 10 OECD economies - Timo Tyrväinen (Bank of Finland, 1995)
Over the past twenty years or so, unemployment has been increasing in most OECD economies.In the same period, there has been a considerable increase in the wedge between the real cost to the employer of hiring a worker and the net real wage received by the worker.The present study examines whether changes in the wedge (including various tax rates) may have generated long-lasting effects on real labour costs.Behaviour which generates this kind of outcome is called "real wage resistance".If there is real wage resistance, higher taxes lead to higher unemployment.If this outcome persists in the long run, the primary problem related to the functioning of the wage setting mechanism is not necessarily the speed of adjustment but rather the equilibrium in which adjustment terminates.The countries examined are the United States, Japan, Germany, France, the United Kingdom, Italy, Canada, Australia, Sweden and Finland.The study covers the private business sector and the estimation method applied is the procedure proposed in Johansen & Juselius (1990) for estimation of long-run relationships.Signs of real wage resistance were discovered in all the economies examined although it differs in degree between countries.Although this can to some extent be related to characteristics of wage setting mechanisms in the countries concerned, there is not a simple story to tell.The outcome depends both on labour market characteristics and on the actual development of the wedge.As far as the effect of actual changes in the wedge on actual changes in unemployment are concerned, the most unfavourable case is that found in France: not only considerable degree of real wage resistance but also a large rise in the wedge was detected.Between the mid-70's and early 90's, the impact of real wage resistance on the unemployment rate is also important in Australia, Canada, Finland and Sweden.In the latter two countries in particular this is due to recent increases in the wedge.When the contribution of taxes is separated it becomes clear that, in Canada unfavourable impacts of real wage resistance are not related to taxation.In Japan, taxes ar? not a primary cause either whereas in France, Italy and Sweden taxes have played a major role.In Germany, appreciation of the exchange rate has "created room" for consumption taxes to rise without the harmful effect on consumer prices which would have generated wage claims.In Finland, large tax increases have taken place in recent years.In the other countries, the effect of taxes on labour cost is in the range of b1 2 per cent.For four countries (Germany, France, Canada and Finland), effects of three alternative revenue-neutral shifts in taxation were simulated.A shift from income tax to payroll tax has no long-run impact but in the short run (which lasts for five years or more) the effect on (un)employment is unfavourable.A shift from taxes on income to taxes on consumption has a favourable impact on (un)employment, not only in the short run but also in the long run. Given current budget constraints, a precondition for this policy option would seem to be that the government allows the real value of such non-wage incomes as pensions, unemployment benefits and social transfers to fall as a result of the increase in the consumption tax.
URN:NBN:fi:bof-20140807655
Keywords: 330